2018
DOI: 10.14238/pi58.6.2018.298-304
|View full text |Cite
|
Sign up to set email alerts
|

Impact of malnutrition on febrile neutropenia in children with acute lymphoblastic leukemia during induction phase chemotherapy

Abstract: Background Acute lymphoblastic leukemia (ALL) is the most common malignancy in children and adolescents. Febrile Neutropenia (FN) is a medical emergency on ALL that often leads to death. Nutrition status assessment on ALL patient is important because malnutrition can reduce the tolerance of chemotherapy, increase incidence of infection and decrease survival rate. Objectives To assess malnutrition as a risk factor for FN in children with ALL. Methods This case-control study was performed at Sardjito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…13 However, Agnes et al found that socioeconomic status was not statistically significant (p=0.83) for FN. 14 In our study, analysis of nutritional status as a risk factor for FN based on anthropometric indices was found statistically significant for, weight for height (≤5 years) p=0.036, OR=0.24 (95% CI .06-.958), weight for age p=0.006, OR=0.23 (95% CI=0.07-0.67), but for BMI for age (>5 years) p=0.28, OD=0.28 (95% CI=0.02-3.19), and height for age p=0.513, OD=0.66 (95% CI-0.18-2.33). In this study, nutritional status was associated with adverse outcomes of FN, but we did not find it as a strong risk factor, as the odds ratio was not significant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 However, Agnes et al found that socioeconomic status was not statistically significant (p=0.83) for FN. 14 In our study, analysis of nutritional status as a risk factor for FN based on anthropometric indices was found statistically significant for, weight for height (≤5 years) p=0.036, OR=0.24 (95% CI .06-.958), weight for age p=0.006, OR=0.23 (95% CI=0.07-0.67), but for BMI for age (>5 years) p=0.28, OD=0.28 (95% CI=0.02-3.19), and height for age p=0.513, OD=0.66 (95% CI-0.18-2.33). In this study, nutritional status was associated with adverse outcomes of FN, but we did not find it as a strong risk factor, as the odds ratio was not significant.…”
Section: Resultsmentioning
confidence: 99%
“…9 Although malnutrition is a common occurrence in children with ALL in our country, there is a dearth of studies exploring the role of nutritional status in patients suffering from ALL, as malnutrition increases the incidence of infection and decreases the survival rate. 10 Thus, this topic was selected to assess the effect of malnutrition on adverse outcomes among ALL patients suffering from FN.…”
Section: Introductionmentioning
confidence: 99%
“…However, an association to hyperglycemia was not apparent [ 8 ]. Nevertheless, malnutrition has been repeatedly described as a predisposing factor for FN [ 11 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, malnutrition causes hematopoiesis, anemia, leukopenia, significant decreases in bone marrow, including IL-6 and TNF-α production, as well as hormonal disturbances. 23,24 Nevertheless, we need to consider the wide confidence interval of the nutrition groups relative risk and seemingly protective effect of obesity as the result of unbalanced numbers of subjects compared to their normal weight counterpart. Therefore, the RR needed to be interpreted carefully.…”
Section: Discussionmentioning
confidence: 99%